Emotional and physical experiences of people with neovascular age-related macular degeneration during the injection process in Germany: a qualitative study - Oliver Zeitz; Martina Breuning; Christine Holmberg; Christian Wolfram; Anne Thier (BMJ Open)
Objectives In order to better understand the continued barriers to the provision of vascular endothelial inhibitor therapy, this study aims to investigate patients’ experiences with neovascular age-related macular degeneration (nvAMD) in Germany during the injection process and how they deal with it.Design and participants This analysis is part of the qualitative arm of a wider mixed-methods study. We recruited participants all over Germany via ophthalmologists, eye clinics, general practitioners, care bases and support groups between June 2018 and December 2020 and selected a subsample of study participants with nvAMD who were either undergoing or had previously undergone vascular endothelial growth factor inhibitor therapy. We conducted narrative, semistructured, face-to-face interviews at the participants’ homes, which were audio-recorded. The interviews were thematically analysed.Results Twenty-two participants were included in this analysis. Experiencing neovascular macular degeneration was dominated by the injection experience. Study participants perceived the treatment with vascular endothelial inhibitor injections as uncomfortable, and they described undergoing varying levels of anxiety during the whole injection process. After some years of receiving multiple injections, the pain and not experiencing any positive effects made participants with significant vision loss want to discontinue therapy. Furthermore, they narrated negative injection experiences in association with their interactions with medical staff and doctors.Conclusion Although time in the medical setting is limited, efficient and good doctor-patient relationships seem crucial for satisfying care experiences. A respectful and humane relationship may be one key to achieving treatment adherence.